Actividad física y su influencia en el sobrepeso y obesidad en los niños de la Escuela Municipal La Pradera - Luna Ordóñez, Katherine Andrea (2019)
The overweight and obesity are metabolic, chronic, and complex illnesses that has effected the entire world. They are considered as one of the most severe public health problems in century XXI since its prevalence has increased intensively. The principal objective of the present research was to evaluate the relation between the development of physics activity with the overweight and obesity on children at “La Pradera Municipal School”. It is about a descriptive and transversal study with a sample of 132 female and male scholar children, in which, the survey technique was used. The obtained results were entered to the Statistical Package for the Social Sciences SPSS program where was concluded that the overweight and obesity are evidenced on ages between 6 and 9 years old resulting the 44.7%, while the biggest prevalent group is between 10 and 12 years old with the 55.3%. On the other hand, it was noticed that in relation with the children sex, the overweight and obesity are more notorious on girls with the 63.2% while boys reflect the 36.8%. Related to the physic activity, the studied population concluded that the 89.4% does do some type of physic activity, while the 10.6% does not. Regarding the relation between physic activity with the overweight and obesity, according to the Chi-Square application, the proposed null hypothesis is rejected in the current study. Key words: physic activity, obesity, overweight, children.